Effects of patella tendon and hydrostatic ankle foot orthoses on foot plantar pressure and pain: Pilot study in healthy subjects - Suvipalawat, Chotika; Amattayakul, Marisa; Pinitlertsakun, Jutamat; Mella, Anna; Polhan, Nattapong; Asanka, Buddhika; Paranavithana, Harsha Hemal; Wairuntahnunnut, Naphuwadol (Science, Engineering and Health Studies, 2025)
This study compared the efficacy of three ankle-foot orthosis (AFO) designs: patellar tendon bearing AFO (PTB-AFO), hydrostatic AFO (H-AFO), and hydrostatic AFO with a four-ply sock (H4-AFO). The research explored pressure distribution on the leg and foot, potential correlations with gender, body mass index (BMI), body fat percentage, and pain scores between PTB-AFO and H4-AFO. Six healthy participants were included, and the study revealed that PTB-AFO effectively reduced plantar pressure, while H-AFO displayed lower average leg pressure than H4-AFO. A significant negative correlation was identified between BMI and average leg pressure in PTB-AFO. However, PTB-AFO was associated with higher discomfort, likely due to its structural design. These findings highlight the need for further investigations involving larger sample sizes and dynamic gait analyses to better understand the impact of orthosis design on pressure distribution and user comfort. This study suggests potential improvements in AFO design that could enhance patient experience and orthotic effectiveness in clinical applications.